リュツォ・ホルム ワン エンガン ポリニア イキ ニオケル カイヒョウ セイサン ト タイリュウ コンゴウ - 牛尾, 収輝; ウシオ, シュウキ; 滝沢, 隆俊; タキザワ, タカトシ; 大島, 慶一郎; オオシマ, ケイイチロウ; 河村, 俊行; カワムラ, トシユキ; Ushio, Shuki; Takizawa, Takatoshi; Ohshima, Kay I.; Kawamura, Toshiyuki (1997)
P(論文) 南極リュツォ・ホルム湾周辺における海洋観測データを用いて, 大陸沿岸に形成されるポリニヤ(海氷野内の開水面または薄氷域)の海洋構造の特性を調べた。この沿岸ポリニヤ域では, 人工衛星画像や航空機からの目視観測結果によると, ほぼ通年にわたって開水面が形成されており, 冬季は新成氷が生産され続けていること, 海洋上層の水温は結氷温度に達していることがわかった。また, ポリニヤ域の対流混合層は, 沖合流氷域のそれよりも厚く発達している。さらに, 対流混合層内の溶存酵素量データから, 深層水の取り込み(entrainment)が生じている可能性も示唆された。 A coastal polynya often forms around Lutzow-Holm Bay even in severe winter. To clarify the characteristics of oceanic structure in the polynya, the water mass of the convective-mixed layer was analyzed. Haline convection by the high ice production in the winter polynya contributes to the formation of a thicker mixed layer than that in the pack ice region. Furthermore, the active convection leads to entrainment of the oxygen-poor deep water underlying the winter mixed layer. Consequently, in the polynya located over the continental shelf break, the oxygen content of the mixed layer is somewhat lower than that in the other polynya, Breid Bay, where haline convection reaches only to the shallow sea bottom of the continental shelf. departmental bulletin paper